USING LOCAL TECHNOLOGIES IN THE PROCESS OF RICE DRYING (American Journal of Business Management, Economics and Banking, 2022)
The article provides information on improvisation of agricultural lands in Uzbekistan, the using local technologies in the cultivation of rice, protecting rice from external factors during the drying process.